2021
DOI: 10.1016/j.jobe.2020.101636
|View full text |Cite
|
Sign up to set email alerts
|

Numerical evaluation of the reliability of using single-story substructures to study progressive collapse behaviour of multi-story RC frames

Abstract: Progressive collapse is a global failure for a multi-story building. All stories above the removed column will consequently deform and help redistribute the loads initially withstood by the removed column. However, due to cost and excessive time to be involved, the majority of existing experimental researches regarding progressive collapse rely on single-story beam-column substructures or sub-assemblages. To date, how to use the results from single-story substructures or sub-assemblages to fully or confidently… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 25 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…And the yield 125 surface is formed based on three stress invariants J1, J'2, and J'3. Previous studies [19][20][21][22][23] found that 126 erosion criterion based on the maximum principal strain is a suitable way to simulate concrete crushing of concrete after adjustments is shown in Fig. 7.…”
Section: Materials Model 120mentioning
confidence: 99%
See 4 more Smart Citations
“…And the yield 125 surface is formed based on three stress invariants J1, J'2, and J'3. Previous studies [19][20][21][22][23] found that 126 erosion criterion based on the maximum principal strain is a suitable way to simulate concrete crushing of concrete after adjustments is shown in Fig. 7.…”
Section: Materials Model 120mentioning
confidence: 99%
“…tensile membrane action (TMA) in slabs [20,21]. Zhou et al [4] conducted a series of static tests on a one-third scaled RC specimen and two PC specimens using dowel bars and corbel to investigate the load transfer mechanisms of these specimens under a middle column loss.…”
Section: Captions Of Figures 434mentioning
confidence: 99%
See 3 more Smart Citations